ROLE OF TRANSVAGINAL ULTRASOUND IN IDENTIFYING ENDOMETRIAL HYPERPLASIA - Nazim, Fatima; Hayat, Zartaj; Hannan, Abdul; Ikram, Umar; Nazim, Khola (Journal of Ayub Medical College Abbottabad, 2013)
Background: Transvaginal sonography (TVS) is one of the diagnostic modalities used to evaluate endometrial pathologies in women with abnormal uterine bleeding. It permits use of high frequency ultrasound waves at greater proximity to the uterus. This study aimed at determining the diagnostic accuracy of TVS in identifying endometrial hyperplasia by comparing with histologic findings in perimenopausal women with abnormal uterine bleeding. Methods: This cross-sectional study was conducted in Department of Obstetrics & Gynaecology, Unit II, Fauji Foundation Hospital, from Sep 2011 to Mar 2012. A total of 263 perimenopausal women aged 40-50 years with abnormal uterine bleeding in the form of menorrhagia, metrorrhagia and polymenorrhagia were enrolled. Thickness of the endometrium was first measured by ultrasound and then was later confirmed by sampling of endometrium. The outcome was measured in terms of accurately diagnosing endometrial hyperplasia by TVS and then using histologic findings as gold standard to confirm. Results: The mean age of selected patients was 45.3±3.2 years. Out of total 263 cases, 129 (49.0%) presented with menorrhagia, 120 (45.6%) presented as metrorrhagia while 14 (5.3%) had polymenorrhagia. The sensitivity and specificity of TVS was 100.0% and 63.7% respectively. Similarly positive predictive value (PPV) and negative predictive value (NPV) were 56.3% and 100.0% respectively. Diagnostic accuracy of TVS in identifying endometrial hyperplasia using histopathology as gold standard was found to be 75.6%. Conclusion: TVS has a moderate diagnostic accuracy in detecting endometrial hyperplasia. Due to the fact that transvaginal ultrasound is safe, acceptable and easily available in most secondary and tertiary care settings and is non-invasive in nature, in our opinion TVS is to be used as a 1st line diagnostic tool in patients who present with abnormal uterine bleeding. Keywords: Diagnostic accuracy, TVS, endometrial hyperplasia, perimenopausal women